The communication dimension of digital media and its role in transmitting knowledge and values - ابراهيم يحياوي (International Journal of Social Communication, 2021)
This study sought to identify the most important dimensions of communication for digital media through its role in transferring knowledge and values and instilling them in the virtual generation, as after the widespread spread of new means of communication, and its multiple, diverse and complex communication implications, it seemed a pioneering role in transferring values and knowledge from one community to another This new manifestation makes our study look for the most important of these dimensions, whether they were educational, social or cultural, which formed virtual societies today and whose effects have become apparent in the social and cultural life of global societies, and our study was adopted on the theoretical side by focusing on A sociological analysis of the phenomenon in order to understand and explain the phenomenon